2012
DOI: 10.1093/infdis/jir875
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral Immunoglobulin-like Proteins Interact With Human Complement Regulators Factor H, FHL-1, FHR-1, and C4BP

Abstract: Leptospira, the causative agent of leptospirosis, interacts with several host molecules, including extracellular matrix components, coagulation cascade proteins, and human complement regulators. Here we demonstrate that acquisition of factor H (FH) on the Leptospira surface is crucial for bacterial survival in the serum and that these spirochetes, besides interacting with FH, FH related-1, and C4b binding protein (C4BP), also acquire FH like-1 from human serum. We also demonstrate that binding to these complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
1
39

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(180 citation statements)
references
References 49 publications
3
137
1
39
Order By: Relevance
“…Based on this assumption, we decided to evaluate whether OmpL1 can also adhere to human PLG in vitro. In addition, we investigated whether the recombinant protein can also bind factor H, human complement, and C4bp, as previously reported for other recombinant proteins (4,5,11,16,71). Our data show that OmpL1 binds to human PLG (P Ͻ 0.01), while no or a very low level of reactivity was detected with the other components and the control proteins (Fig.…”
Section: Reactivity Of Ompl1 With Human and Hamster Leptospirosis Sersupporting
confidence: 64%
“…Based on this assumption, we decided to evaluate whether OmpL1 can also adhere to human PLG in vitro. In addition, we investigated whether the recombinant protein can also bind factor H, human complement, and C4bp, as previously reported for other recombinant proteins (4,5,11,16,71). Our data show that OmpL1 binds to human PLG (P Ͻ 0.01), while no or a very low level of reactivity was detected with the other components and the control proteins (Fig.…”
Section: Reactivity Of Ompl1 With Human and Hamster Leptospirosis Sersupporting
confidence: 64%
“…62 Leptospiral binding proteins to C4BP, factor H, and factor H-like have been identified in Leptospira. 17,18,46,[63][64][65][66] We report that Lsa23 is a novel C4BP and factor H binding protein of Leptospira, although with the ligand affinity for factor H binding protein seems to be low.…”
Section: Discussionmentioning
confidence: 88%
“…Normal human serum (NHS) and purified human FH, C4BP, FI, C3b, C5b6, C7, C8, and C9 were purchased from Complement Technology, and human vitronectin was purchased from Sigma-Aldrich. Recombinant FH fragments SCR8 -14 and SCR15-20 were produced as described previously (7). Goat anti-human FH was purchased from Quidel, rabbit anti-human C4BP was purchased from Calbiochem, and rabbit anti-human vitronectin and goat anti-human C3 and C9 polyclonal antibodies were purchased from Complement Technology.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies on the mechanisms underlying this resistance were only recently initiated. Acquisition of fluid-phase host complement regulators on the surfaces of pathogens is a common complement evasion mechanism, and it has been demonstrated that pathogenic Leptospira strains are able to bind factor H (FH), factor H-like 1 (FHL-1), factor H-related 1 (FHR-1), and C4b binding protein (C4BP) (4)(5)(6)(7).…”
mentioning
confidence: 99%